Telemedicine and its application in telemedicine management - -, MUSTAFA ALMAHDI ALGAET; MUHAMAD NOH, ZUL AZRI; Shibghatullah, Abdul Samad; -, ALI AHMAD MILAD; -, AOUACHE MUSTAPHA (Outskirts Press, Inc., 2014)
Telemedicine can be defined as the extensive depiction of providing medical and healthcare services by using telecommunications structures. Information Technology (IT) which covers controlling, interactive media, pattern recognition, knowledge management, image and signal processing: have empowered an extensive array of telemedicine applications to be supported. The joined consequence of the expansion of the global population and maturing populace in most advanced countries offersascent to an increasing interest on the public health system. The effect on public health systems in various nations were further empowered by a change in the lifestyle and environmental contamination which further increases the demand for health systems. This is obvious from the pattern of perpetual ailments and complication arising from obesity-related conditions which attack youthful individuals over the previous decade. Currently, the financial prosperity which blesses the present generation is a result of the diligent work done by our fore fathers and the rapacious exploitation of the natural resources that will eventually cause various issues to the upcoming generation. Therefore, we should seize the responsibility of caring for the elderly who tirelessly sacrificed their time for the betterment of the current generation. Nevertheless, we are attempting to upgrade medicinal technology to enhance our well-being, and to furnish a supportable healthcare system for the upcoming era. Telemedicine is poised as a means of fulfilling our obligations to the adolescents and the elderly.